NUMERICAL ANALYSIS OF WELDED BEAM-COLUMN JOINTS IN ALUMINUM STRUCTURES (Advances in Civil and Architectural Engineering, 2021)
The objective of this study is to compare the performance for welded beam-column joints in aluminum structures using moment-rotation diagrams and to evaluate the influence of welding on joint rigidity. A nonlinear numerical calculation of welded beam–column joints is performed using the finite element method. Material and geometric nonlinearities were included in the model. The connection was analyzed for two cases: variants with and without welded stiffener plates. Two material models were used. The first was derived from the applicable standard for aluminum structures, while the other was based on the results of a previous material study and calibrated using a separate numerical calculation. From the results of the calculations, moment-rotation diagrams for different geometries and material properties of joints were constructed and compared. The obtained moment-rotation diagrams for the stiffened and unstiffened joints demonstrate that stiffening of the joints in aluminum structures improves the properties of the joint in terms of higher rigidity, resistance, and ductility, regardless of the existence of the heat affected zone.